OPTIMIZING RPG PATHFINDING A HYBRID APPROACH FOR STATIC AND DYNAMIC OBSTACLE AVOIDANCE - Gunawan, Renaldy Ari; Istiono, Wirawan (IJISCS (International Journal of Information System and Computer Science), 2023)
Playing a role The popular game genre known as "RPG" employs a pathfinding algorithm in its operation. The process of discovering a path from one place to another is called pathfinding. Pathfinding algorithms come in a variety of forms and are varyingly efficient. One of these methods is the A-star algorithm, which is frequently used in different games to determine routes and has actually been evaluated for efficiency. An additional algorithm to consider is the dynamic pathfinding algorithm, which is quite tiny for reference and not well-known. Combining these two techniques can result in an algorithm that avoids both static and dynamic barriers in addition to finding the fastest path. The two algorithms will be combined in this research, and two static and dynamic obstacle scenarios will be used for testing. According to the study's findings, the combination of these two algorithms enables the algorithm to avoid both static and dynamic obstacles. However, it should be noted that in the event of a dynamic obstacle, the Non-Player Character (NPC) will need to travel 3.04 seconds longer to reach their destination because they will need to find an alternate route.